Born to teach : a biography of Professor Theophilus Olatunji Taiwo Olowokure - Obialom, Casmiar Uchechukwugaeme (Kaduna, Nigeria : Cashman Press and Boos Company, 2001)
About a Nigerian scholar, Professor Theophilus Olatunji Taiwo Olowokure, who rose from grass to grace through hardwork, dedication to duty, selfless service, honesty, determination and the fear of God.
Includes bibliographical references.
oif 15/04/15
Loan
Keywords: Olowokure, Theophilus Olatunji Taiwo; Teachers -- Biography; Teaching -- Anecdotes